Solution structure and dynamics of the mitochondrial‐targeted GTPase‐activating protein (GAP) VopE by an integrated NMR/SAXS approach. (28th April 2022) - Smith, Kyle P.; Lee, Woonghee; Tonelli, Marco; Lee, Yeongjoon; Light, Samuel H.; Cornilescu, Gabriel; Chakravarthy, Srinivas
Abstract: The bacterial pathogen Vibrio cholerae use a type III secretion system to inject effector proteins into a host cell. Recently, a putative Toxic GTPase Activating Protein (ToxGAP) called Vibrio outer protein E (VopE) was identified as a T3SS substrate and virulence factor that affected host mitochondrial dynamics and immune response. However, biophysical and structural characterization has been absent. Here, we describe solution NMR structure of the putative GTPase‐activating protein (GAP) domain (73–204) of VopE. Using size exclusion chromatography coupled with small‐angle x‐ray scattering and residual dipolar coupling data, we restrained the MD process to efficiently determine the overall fold and improve the quality of the output calculated structures. Comparing the structure of VopE with other ToxGAP's revealed a similar overall fold with several features unique to VopE. Specifically, the "Bulge 1, " α1 helix, and noteworthy "backside linker" elements on the N‐terminus are dissimilar to the other ToxGAP's. By using NMR relaxation dispersion experiments, we demonstrate that these regions undergo motions on a > 6 s −1 timescale. Based on the disposition of these mobile regions relative to the putative catalytic arginine residue, we hypothesize that the protein may undergo structural changes to bind cognate GTPases. Abstract : PDB Code(s): 6X6N ;